Remains. On Survivance in Translation and Literary Criticism - Agnieszka Pantuchowicz (Anglica. An International Journal of English Studies)
The article proposes a reading of Jacques Derrida’s concept of “remains” as a way of approaching the question of being true to the original both in translation and in critical readings of texts that seem to assume the unchangeable presence of their objects of attentiveness. Although I mainly concentrate on the issues of translation, the affinities between the two spheres of literary interest are only too obvious, and I gradually approach them in this paper through Derrida’s reading of what seems to be an Alaskan case of coffining of the dead. This coffining, as way of treating remains, is rhetorically related to reading and interpretation, and also to translation, as a tribute to what is left behind, unspoken or untranslated. What I attempt to bring to the fore in this paper are the complexities and intricacies involved in linguistic and artistic mythologies of presenting and articulating the world as simply present and living, at the cost of discursively coffining what remains.